Preparation and evaluation of metronidazole-loaded pectin films for potentially targeting a microbial infection associated with periodontal disease - Taepin Junmahasathien (2018)
© 2018 by the authors. The objective of this study was to develop the metronidazole loaded high and low methoxyl pectin films (HM-G-MZ and LM-G-MZ) for the treatment of periodontal disease. The films were prepared by pectin 3% w/v, glycerin 40% w/v, and metronidazole 5% w/v. The developed films were characterized by scanning electron microscope and evaluated for thickness, weight variation, and elasticity. The developed films showing optimal mechanical properties were selected to evaluate radial swelling properties, in vitro release of metronidazole and the antimicrobial activity against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans by the disc diffusion method. The results demonstrated that LM-MZ and HM-G-MZ films were colorless and yellowish color, respectively, with the film thickness around 0.36-0.38 mm. Furthermore, both films exhibited good elasticity with low puncture strength (1.63 ± 0.37 and 0.84 ± 0.03 N/mm2, respectively) and also showed slight increase in radial swelling, so that they could be easily inserted and fitted into the periodontal pocket during a clinical use. However, HM-G-MZ showed a decrease in radial swelling after 1 h due to the film erosion. The in vitro release study of LM-G-MZ showed a burst release that was initially followed by a slow release rate profile, capable to maintain the therapeutic level in periodontal pocket for seven days, whereas HM-G-MZ showed an immediate release profile. The cumulative percentage of metronidazole release from HM-G-MZ was less than LM-G-MZ during the first 5 min as metronidazole was in a crystalline form inside HM-G-MZ film. For antimicrobial activity test, both films showed the inhibitory effect against P. gingivalis and A. actinomycetemcomitans, and there was no difference in the inhibition zone between LM-G-MZ and HM-G-MZ. The present study showed, for the first time, that low methoxyl pectin film containing glycerin and metronidazole could be potentially considered as a promising clinical tool for the drug delivery via intra-periodontal pocket to target an oral disease that is associated with polymicrobial infection.